Facilitators of and Barriers to Successful Implementation of the One Key Question? Pregnancy Intention Screening Tool - Meron Ferketa; Kellie Schueler; Bonnie Song; Francesca Carlock; Debra B. Stulberg; Emily White VanGompel (Mary Ann Liebert, 2022)
Background: One Key Question? (OKQ) is a tool that embeds a patient-centered screening into routine visits with the goal of making pregnancy intention screening universal, but widespread implementation has not yet been adopted. We aimed to explore the barriers and facilitators of OKQ implementation to better understand how to best implement the tool across different settings. Methods: We invited staff and clinicians from one obstetrics and gynecology clinic and one family medicine clinic, which previously implemented OKQ, to complete surveys and qualitative interviews about their experiences with the tool. The interview guide and thematic analysis of the interview transcripts were informed by the Consolidated Framework for Implementation Research (CFIR). Main Findings: Major facilitators of OKQ implementation are the simplicity of the tool, engagement of clinic leadership, and compatibility between the perceived goals of the tool and those of practice staff and clinicians. Although participants indicated that OKQ had a minimal impact on clinic workflow during its implementation, preimplementation time concerns were a major barrier to implementation in both clinics. Barriers seen in the family medicine practice included OKQ distracting from the visit agenda, and concerns about the OKQ gold standard protocol of screening each patient at every visit. Participants even suggested asking OKQ only during annual check-up appointments. Conclusions: The perceived alignment between the tool's goals and those of clinic stakeholders was an important facilitator of OKQ implementation success. However, characteristics of the clinic setting, such as competing medical priorities and time constraints, influenced initial attitudes toward the feasibility of the intervention. Clinical Trial Registration Number: NCT03947788